To Understand the Target Consumer Profile for the New Launch of Sunfeast Marie Light & Addittionally Understand the Consumer Perception for the Brand Sunfeast - Nenwani Pooja (2k81111) (Pune University Pune, 2010)
Gaikwad Jyoti